Compound Heterozygous Hemoglobin SD Disease Presenting as Sickle Cell Crisis in Pregnancy - Rakhi; Minakshi, Rohilla; Pankaj, Malhotra; Reena, Das; Vanita, Jain; GRV, Prasad; Jasvinder, Kalra (Journal of Women's Reproductive Health, 2016)
A case report of compound heterozygous hemoglobin SD disease presenting as sickle crisis during pregnancy. The discussion covers transfusion, pain control, and peripartum care.